Quinone Contents in Teak Heartwood Isolated by Cold Extraction - Ganis Lukmandaru (Jurnal Ilmu dan Teknologi Kayu Tropis, 2015)
Sampling by increment borer along with wood extraction by cold soaking would be useful for large sample size and if the destructive sampling is undesirable. This work aimed to evaluate the reliability of cold extraction by methanol and acetone to extract the quinone compounds of teak heartwood compared to the conventional soxhlet extraction by ethanol-benzene. Another purpose of this work was to find out the intra-tree variability of quinone compound around the outer heartwood parts (8 angles, 16 points). On the basis of the yield of ethanol-benzene extracts in 6 trees, cold extraction could remove the extracts of 37-66% by methanol and 23-61% by acetone. By correlaton analysis, considerable degree of correlations (r>0.9) were calculated between soxhlet and cold extraction in the contents of deoxylapachol, lapachol, tectoquinone. With regard to intra-tree variation quinones, wide level ranges were observed in all compounds by judging the coefficient of variation, except for tectol. Therefore, it is suggested that the sampling in the tangential direction in a single tree should be taken at 3 points separated by at least 90 degrees to avoid the bias in the individual components. The variation of quinone total amounts, however, showed comparatively low (18%) of coefficient of variation.Keywords: cold extraction, extractives, incrrement borer, quinone, Tectona grandis